INDIGENOUS KNOWLEDGE OF THE CO TU ETHNIC GROUP FOR MEDICINAL PLANTS USED IN THE TAY GIANG DISTRICT (AXAN AND TR’HY COMMUNE), QUANG NAM PROVINCE, VIETNAM - Ngoc Huyen, Dang; Dinh Duy, Vu; Xuan Dac, Le; Mai Phuong, Pham (Journal of Forestry Science and Technology, 2023)
The Co Tu people in two communes Axan and Tr’Hy, Tay Giang district, Quang Nam have rich experience in using medicinal plants because their life have been based on the forest resources. In this article, we discuss the medicinal plants in the following key points: usage, parts used, and disease groups used. The data collection methods in this study includes the specimen collection, the interview method, while the identification of the species name, the method of medicinal plant resources diversity assessment and the method of endangered medicinal plants level assessment are employed in this work. The initial investigation shows that the medicinal plants in this area consisted of 59 species, 54 genera, 41 families, which are belonged to three vascular divisions under the names: Polypodiophyta, Pinophyta and Magnoliophyta. Moreover, roots and tubers of these medicinal plans are two most popularly used parts by the ethnic minorities of Co Tu. People there often use medicinal plants in traditional medicine practices, particularly in treatments of the arthritis and diseases of the digestive system. Finally, seven species of medicinal plants found here are listed in the Vietnam Red Data Book (2007), the IUCN Red list 2022 and the Government Degree No 84/2021/ND-CP of the Socialist Republic of Vietnam.